Effectiveness of exercise on musculoskeletal function and clinical outcomes in patients with diabetic peripheral neuropathy: a systematic review and meta-analysis - Yang, Jin; Li, Li; Ye, Ting; Pu, You; Yao, Qian; Luo, Jian; Huang, Yunman; Zhang, Xianqin; Yang, Zheng (Frontiers in Neurology, 2025)
BackgroundDiabetes mellitus is a major public health issue, and its complication, diabetic peripheral neuropathy (DPN), can significantly impair foot and ankle joint function, affecting daily activities and quality of life. This systematic review and meta-analysis aimed to evaluate the impact of exercise on musculoskeletal function and clinical outcomes in DPN patients.MethodsEvaluation of randomized controlled trials (RCTs) of exercise in patients with DPN published from Cochrane Library, PubMed, Embase, Web of Science, Medline, ClinicalKey, CNKI, Wanfang database, VIP Chinese Journal Database, and Chinese Biomedical Literature Database was performed. Revman 5.4 software was used for statistical analysis.ResultsA total of 625 samples were included in 10 studies. It showed that exercise significantly increased ankle dorsiflexion range of motion (SMD = 0.61, 95%CI (0.13, 1.08), P < 0.05), ankle flexion range of motion (SMD = 0.59, 95% CI (0.12, 1.06), P < 0.05), hallux strength (MD = 1.89, 95% CI (1.00, 2.78), P < 0.001), toes strength (MD = 2.51, 95% CI (1.69, 3.33), P < 0.001) and lower extremity functional strength (MD = −2.82, 95% CI (−3.88, −1.76), P < 0.001), whereas reduced glycosylated hemoglobin (SMD = −1.44, 95% CI (−2.30, −0.57), P < 0.01) and body mass index (MD = −0.86, 95% CI (−1.15, −0.57), P < 0.001). However, discrepancies were observed between pooled results based on different neuropathy assessment tools.ConclusionThe available evidence suggests that exercise training is an effective method for improving peripheral neuropathy.Systematic review registrationhttps://inplasy.com/, identifier INPLASY202340112.